Knowledge management in agro-industrial productive chains: An initial discussion - Jorge, Carlos Francisco Bitencourt; Machado, Joao Guilherme de Camargo Ferraz [UNESP]; Cazane, Ana Lívia [UNESP] (IGI Global, 2021)
The main objective of this chapter is to foster the discussions on the perspectives and actions of knowledge management and use in agribusiness, especially in the coordination of agro-industrial production chains, or in the so-called agrifood systems, connecting agribusiness professionals and researchers under knowledge management and use in this context, without, however, ending the discussion. The adequate management of information and its rapid transfer within the agrifood system is a competitiveness factor, as trust and cooperation are elements which enhance knowledge construction, resulting in the consideration, by companies, of articulation forms, in addition to organizational boundaries. It is believed that knowledge management, applied in the production chains coordination, will have an important role in overcoming the challenges generated by the pandemic the world is going through.